A Novel UX-Centered ITSM Framework for Technology Startups: Beyond Traditional Service Management - Marcel, Marcel; Marzuqi, Tubagus Ahmad (Journal of Information System and Informatics, 2025)
This research explores the integration of User Experience (UX) principles into IT Service Management (ITSM) frameworks within resource-constrained B2B SaaS technology startups. Through a comprehensive qualitative case study methodology involving semi-structured interviews with seven stakeholders, participatory observation across 12 sessions, and systematic document analysis at a Jakarta-based startup serving SMEs, we uncovered a critical paradox: companies selling superior UX solutions to clients often neglect these principles in internal IT management. The primary contribution is a novel adaptive UX-Centered ITSM conceptual model featuring three interconnected layers: Core Principles, Implementation Domains, and Operational Elements, designed for incremental implementation based on startup capacity. Unlike rigid existing ITSM frameworks, this model introduces a prioritized approach with "Must Have," "Should Have," and "Can Be Added" categorizations specifically tailored for startup contexts. The research identified five contextual factors influencing implementation: organizational culture, leadership structure, resource limitations, team dynamics, and SME client characteristics. Findings reveal that UX-centered ITSM not only addresses internal operational challenges but creates strategic alignment between internal practices and external value propositions, forming the foundation for market credibility and business sustainability. This framework provides startup managers and IT practitioners with an actionable roadmap for transforming ad-hoc internal systems into user-centered services that support operational excellence while enhancing competitive positioning in digital transformation markets.